From primoroliality to pop nationalism Anglo-Saxon theoretical background of nationalism and the nation = Od prymordializmu do popnacjonalizmuAnglosaskie ujęcia teoretyczne nacjonalizmu i narodu - Grygo, Błażej (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The main task of this paper is to present the most important paradigms operating in the social sciences in the Anglo-Saxons cultural circle after World War II. The paradigms overview starts from Primordialism discourse through Perennialism, Modernism toward Ethno-symbolism and Banal Nationalism melted into Pop cultural social behaviors. A series of debates on the description and operationalization of knowledge on titled is-sue has already been taken. What is more, chapter shows the concept of divers approach toward nationalism theory which still seems to be a novelty at the Central and Eastern European discourse.
Keywords: naród; teoria nacjonalizmu; popnacjonalizm; Theories of Nationalism; nation; Pop-Nationalism